Predicting the Shear Strength of Unfilled Rock Joints with the First-Order Takagi-Sugeno Fuzzy Approach - Matos, Yago Machado Pereira de (2022)
As a result of a number of studies, some analytical models have been developed to predict the shear behavior of unfilled rock joints, but they all present a purely deterministic nature because their input variables are defined without considering the uncertainties inherent in the formation processes of the rock masses and related discontinuities. This work aims to present a model for predict the shear strength of unfilled rock joints by incorporating uncertainties in the variables that govern its shear behavior with a First-Order Takagi-Sugeno fuzzy controller. The model is developed based on the results of 44 direct shear tests carried out on different types of joints. The model input variables are the normal boundary stiffness and initial normal stress acting on the joint, its roughness (expressed by the JRC value), the uniaxial compressive strength, the basic friction angle of the intact rock and the shear displacement imposed to the joint. The results show that the predicted shear strength of unfilled rock joints obtained by the fuzzy model fits satisfactorily the experimental data and allows the shear behavior of the discontinuities to be defined. A practical application of the model in a stability analysis of a rock mass is also presented.